Shortest path simulation using interactive SVG map - Jonathan, Sidi; Kiew, Wei Fa; Syahrul Nizam, Junaini (IEEE, 2009)
This paper presents reports a design and development of the interactive map using Scalable Vector Graphics (SVG) that can be used to find the shortest path. Using our interactive map, the user will be able to set the route or path to the desired location. If that path is congested, the map will find the second shortest path to the user. In the usability study, we have tested the map with the mean value of 4.76 out of 5.